2019
DOI: 10.1016/j.ekir.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation Precedes Microalbuminuria in Diabetes

Abstract: AimThe aim of the case-control study was to investigate if serum biomarkers indicative of vascular inflammation and endothelial dysfunction can predict the development of microalbuminuria in patients with diabetes mellitus type 2.MethodsAmong participants enrolled in the ROADMAP (Randomized Olmesartan And Diabetes MicroAlbuminuria Prevention) and observational follow-up (OFU) studies, a panel of 15 serum biomarkers was quantified from samples obtained at initiation of the study and tested for associations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 75 publications
1
42
0
Order By: Relevance
“…Reactive Oxygen Species (ROS) and subsequent cellular damage trigger induction of glucose homeostasis transcriptional factors, the proinflammatory cytokines (such as IL-1β), and growth factors (such as TGF-β1) [4][5][6]. The mechanism by which oxidative stress can induce apoptosis may involve increased peroxidation of membrane lipids, increased oxidative injury to macromolecules, changes in cellular redox potential, or depletion of glutathione [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive Oxygen Species (ROS) and subsequent cellular damage trigger induction of glucose homeostasis transcriptional factors, the proinflammatory cytokines (such as IL-1β), and growth factors (such as TGF-β1) [4][5][6]. The mechanism by which oxidative stress can induce apoptosis may involve increased peroxidation of membrane lipids, increased oxidative injury to macromolecules, changes in cellular redox potential, or depletion of glutathione [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This will allow us to investigate whether SR imaging is able to detect alterations in the microvascular architecture at the early stages of their occurrence. If early or subtle microvascular alterations have a prognostic value and could allow timely initiation or change of treatment, e.g., in persons who are developing diabetic nephropathy but do not yet show other clinical signs of disease [ 41 ], or in persons undergoing cancer treatment where early readouts of drug or radiation efficacy are crucial [ 42 ], ultrasound SR imaging could fill an unmet need and evolve into a strong tool in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…The EMT is characterized by the loss of epithelial markers such as cytokeratin and E-cadherin, and by nuclear translocation of β -catenin accompanied by expression of mesenchymal markers such as vimentin and α -smooth muscle actin ( Tanabe et al, 2020 ). In patients with T2DM, elevated plasma levels of TGF- β 1, CXCL-16 and angiopoietin-2 have been shown as independent predictors of albuminuria and these molecular markers can improve renal risk models beyond established clinical risk factors ( Scurt et al, 2019 ). Through the direct inhibition of Mmp-9 using a neutralizing antibody in a murine model of unilateral ureteral obstruction, Tan et al (2013) have suggested a potential mechanism underlying the contribution of Mmp-9 to kidney fibrosis: (1) Mmp-9 cleaves osteopontin; (2) osteopontin plays a key role in macrophage recruitment; (3) infiltration of macrophages; (4) tubular cell EMT and (5) kidney fibrosis.…”
Section: Discussionmentioning
confidence: 99%